Sustainable Urban Mobility Plan for Istanbul: A Critical Review - Canitez, Fatih (Journal of Intelligent Decision Making and Information Science, 2025)
The concept of a sustainable urban mobility plan (SUMP) for cities was first developed to address the shortcomings of conventional transport planning with its focus on accessibility, social equity, environmental quality, and an integrated development of all transport modes as well as an involvement of stakeholders and citizens through a transparent and participatory approach. Since its development in early 2010s, many European cities have adopted this concept for their mobility planning. The sustainable mobility literature already includes many examples and reviews of SUMPs which have been implemented at various cities across Europe. Having implemented the SUMP concept in 2022, the city of Istanbul, having a population of around 16 million people, offers a novel case in terms of the complexity of urban issues addressed. This paper reviews Istanbul’s sustainable urban mobility plan, discussing the benefits as well as shortcomings for achieving a sustainable mobility transition in Istanbul. The review provides many highlights that would be helpful for other cities going through a similar transition.